Who owns the land? Social relations and conflict over resources in Africa - Sara S. Berry (Freie Universität Berlin, Junior Research Group 'Global Change - Local Conflicts' (GLOCON), 2018)
Using case studies drawn from the authors' own and others' research, this working paper describes and compares some of the ways land conflicts reflected, intensified or reshaped struggles over authority within and between families, local communities, institutions and states in post-colonial Africa. In the past, many Africans gained access to land through membership in a social group, rather than freehold ownership. In recent decades, with rising demand for land, urgent questions arose about land tenure and debates over land transactions often turned on issues of authority. Who was entitled to sell, lease, mortgage or bequeath land or land use rights to others, and who could decide? Coinciding with Africans' struggles to work out the conditions of their own self-government following the end of colonial rule, rising competition over land intersected with conflicts over authority and obligation at all levels of social interaction. This essay will focus on processes of 'privatisation from below', asking how smaller-scale commercial acquisitions figure as sources of wealth and/or threats to livelihood in different economic and political contexts – – Das Working Paper beschreibt und vergleicht einige der Formen, wie sich Kämpfe um Autorität in und zwischen Familien, lokalen Gemeinschaften, Institutionen und in Staaten im postkolonialen Afrika in Konflikten um Land widerspiegelten, intensivierten oder veränderten. Dabei bezieht sich die Autorin auf Fallstudien aus ihrer eigenen und anderer Forschung. Früher bekamen viele Afrikaner_innen Zugang zu Land eher über die Mitgliedschaft in einer sozialen Gruppe als über individuelles Eigentum. In den letzten Jahrzehnten, mit der wachsenden Nachfrage nach Land, kamen wichtige Fragen in Hinblick auf Landbesitz auf und Debatten über Landtransaktionen widmeten sich zunehmend dem Thema Autorität. Wer war berechtigt Land oder Landrechte zu verkaufen, zu verpachten, zu verpfänden oder zu vererben und wer konnte das entscheiden? Die gleichzeitige Suche nach den Bedingungen einer eigenen Regierungsweise nach Ende der Kolonialherrschaft führte dazu, dass sich die zunehmende Konkurrenz um Land mit Konflikten um Autorität und Zwang auf allen Ebenen der sozialen Interaktion verband. Dieser Artikel betrachtet Prozesse der "Privatisierung von unten" und fragt danach, wie kleinere kommerzielle Aneignungen als Basis für Wohlstand und/oder Bedrohung der Lebensgrundlage in verschiedenen ökonomischen und politischen Kontexten fungieren.
Keywords: 330; land ownership; land rights; social relations; authority; Landbesitz; Landrechte; soziale Beziehungen; Autorität